The Gospel of Judas in context : proceedings of the First International Conference on the Gospel of Judas, Paris, Sorbonne, October 27th-28th, 2006 - Scopello, Maddalena. (Nag Hammadi and Manichaean Studies ;, 2008)
The papers gathered in this book were presented at the First International Conference (held in Paris, University of Sorbonne, October 27th-28th 2006), devoted to the newly discovered Gospel of Judas, preserved in the 4th century Coptic Codex Tchacos. These essays explore several crucial literary, historical and doctrinal issues related to this gospel, composed in the second half of the 2nd century. This unexpected discovery sheds a new light on the role attributed to Judas by some Gnostic Christian movements. A hotly debated question is precisely the significance of Judas in this gospel: hero or villain? Special attention is given to the sources - Greek, Jewish, Christian and even Iranian - used by the unknown author. This book will be of special interest for historians of late Antiquity religions and scholars in New Testament studies, Gnosticism and Coptic literature.